1997
DOI: 10.1111/j.1536-7150.1997.tb03460.x
|View full text |Cite
|
Sign up to set email alerts
|

Economics and Restaurant Gratuities: Determining Tip Rates

Abstract: IS tipping in restaurants simply a social norm where people tip on the basis of some rule of thumb (15% of bill size for example)? Using evidence gathered from surveys of nearly 700 diners in 7 Minnesota restaurants, it is argued that tipping is both a social norm and a means of rewarding good service. Survey evidence suggests that diners use rules of thumb as starting points and then vary gratuities on the basis of service just received, expected future service, whether they dine alone or with a group, alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 8 publications
7
64
0
Order By: Relevance
“…Previous empirical studies have confirmed this prediction (see in particular Bodvarsson and Gibson (1997) and Lynn and McCall (2000)). However, we now test for other features of an efficient tipping contract.…”
Section: Tips Depend On Service Qualitysupporting
confidence: 67%
See 1 more Smart Citation
“…Previous empirical studies have confirmed this prediction (see in particular Bodvarsson and Gibson (1997) and Lynn and McCall (2000)). However, we now test for other features of an efficient tipping contract.…”
Section: Tips Depend On Service Qualitysupporting
confidence: 67%
“…2 Previous empirical studies have also found that tip increases with service quality (see in particular Bodvarsson and Gibson (1997), and Lynn and McCall (2000)). a simple theoretical model for the determinants of tipping behavior and then investigate whether our observed tipping behavior is consistent with this model.…”
Section: Introductionmentioning
confidence: 99%
“…Lynn and Latané (1984) found no relation. Bodvarsson and Gibson (1997) found a positive relationship in five out of seven restaurants but a negative one in the two other restaurants; the relationship was positive on average but very weak over all seven restaurants. Lynn and McCall (2000) found a positive relationship but it was so weak that they doubted whether waiters and waitresses could really see it in their earnings.…”
Section: Literature Reviewmentioning
confidence: 80%
“…For instance, etiquette guides suggest tipping 15 to 20 % of the bill size in the USA (Lynn, 2006). The empirical studies support this norm: Conlin, Lynn, and O'Donoghue (2003) reported the average gratuity to be 17.5 % of the bill, Lynn and Latané (1984) about 15.5 %, Bodvarsson and Gibson (1997) 15 % (but it differed among restaurants), Bodvarsson, Luksetich, and McDermott (2003) 14.3 %, Lynn, Jabbour, and Kim (2012) 10-16 %, and Harris (1995) about 14 %. However, some researchers found lower gratuities.…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation